Natural and social sciences have to merge? A view from Russia - Yanitsky, Oleg N. (Advances in Social Sciences Research Journal, 2017)
The UNESCO’s Social and Natural Sciences Councils launched a process of the merging of these two Councils aimed at enhancing if interdisciplinary research and education. The paper based on some inquires in the history of science, the author’s long-term experience of participation in the UNESCO’s ‘Man and the Biosphere’ program as well as on some current international interdisciplinary research and developments, analyses the state of affairs in this realm, the impetuses and impediments of the merging process. The author came to conclusion that: (1) it’s not a volitional decision but a reaction on integrating processes embracing all forms of human activity stimulated by the Fourth industrial revolution and rapid development of the information-communication systems embracing all spheres of human activity; (2) this revolution makes our life and its environment more ‘compressed’ and interdepended; (3) we are now in the zenith of technocratic aspirations and predominance of socio-constructivist viewpoint on social and natural processes; (4) some major research findings age gradually replaced by ‘dramatized’ and short-lived news produced by media; (5) global dynamics outstrips research-and-development processes; (6) the objective processes of sciences merging and a tough market competition clash with each other.